2023
DOI: 10.1073/pnas.2201942119
|View full text |Cite
|
Sign up to set email alerts
|

Socio-ecological gap analysis to forecast species range contractions for conservation

Abstract: Conservation requires both a needs assessment and prioritization scheme for planning and implementation. Range maps are critical for understanding and conserving biodiversity, but current range maps often omit content, negating important metrics of variation in populations and places. Here, we integrate a myriad of conditions that are spatially explicit across distributions of carnivores to identify gaps in capacity necessary for their conservation. Expanding on traditional gap analyses that focus almost exclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 65 publications
2
8
0
Order By: Relevance
“…The human-bear interface can also significantly influence Additionally, the diminishing proximity between human settlements and the human-bear interface has intensified the potential for human-bear interactions. This trend aligns with previous studies (Harris et al, 2023) and 2020 (Ji, Wei, Liu, Li, Li, Huang, et al, 2022). Our interview surveys have indicated that most respondents perceive a discernible rise in human-bear interactions over the past two decades.…”
Section: Discussionsupporting
confidence: 90%
“…The human-bear interface can also significantly influence Additionally, the diminishing proximity between human settlements and the human-bear interface has intensified the potential for human-bear interactions. This trend aligns with previous studies (Harris et al, 2023) and 2020 (Ji, Wei, Liu, Li, Li, Huang, et al, 2022). Our interview surveys have indicated that most respondents perceive a discernible rise in human-bear interactions over the past two decades.…”
Section: Discussionsupporting
confidence: 90%
“…The limited research in Oceania can be explained by only eight native terrestrial mammalian carnivore species > 500 g present there, all of which are in the Family Dasyuridae, except the dingo ( Canis dingo ). Carnivores in production forests in Africa remain understudied, despite the continent harbouring about a third of all carnivore species (Harris et al 2022) and 16% of the world’s forests. 60% of all Africa’s forest is not primary forest, indicating forestry is a major land use, though the continent contains only 2% of the world’s plantations (FAO 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The limited research in Oceania can be explained by only eight native terrestrial mammalian carnivore species >500 g present there, all of which are in the Family Dasyuridae, except the dingo (Canis dingo). Carnivores in production forests in Africa remain understudied, despite the continent harbouring about a third of all carnivore species (Harris et al 2022) and 16% of the world's forests. Only 40% of all Africa's forest is unharvested, suggesting forestry is a major land use, though the continent contains only 2% of the world's plantations (FAO 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Carnivores in production forests in Africa remain understudied, despite the continent harbouring about a third of all carnivore species (Harris et al. 2022) and 16% of the world's forests. Only 40% of all Africa's forest is unharvested, suggesting forestry is a major land use, though the continent contains only 2% of the world's plantations (FAO 2020).…”
Section: Discussionmentioning
confidence: 99%